Analisis kesulitan membaca tingkat lanjut dalam pembelajaran bahasa indonesia kurikulum merdeka - Dewi, Mutiara Sari; Rukayah, Rukayah; Kurniawan, Sandra Bayu (Didaktika Dwija Indria, 2023)
The purpose of this study was to describe the advanced reading difficulties experienced by students in learning Indonesian in the independent curriculum of class IV SDN Jajar No 73 Surakarta in the academic year 2022/2023. This research uses descriptive qualitative research. The research subjects were fourth grade students at SDN Jajar No. 73 Surakarta. Data collection techniques in this study were interviews, observation, and document studies. The data analysis technique used is Miles and Huberman's interactive analysis which consists of data reduction, data presentation, verification, and drawing conclusions. The technique for testing the validity of the data uses technical triangulation. Analysis of advanced reading difficulties in learning Indonesian in the independent curriculum, found that fourth grade students still had difficulty learning advanced reading, especially at the creative reading level. The internal causal factors are learning motivation and language development. External causal factors are culture and environment. Efforts that can be made to help students' difficulties are by means of additional learning media with independent curriculum projects, using learning strategies that further develop student creativity, getting used to literacy programs.